2010
DOI: 10.1111/j.1582-4934.2009.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Small, dense HDL 3 particles attenuate apoptosis in endothelial cells: pivotal role of apolipoprotein A‐I

Abstract: Plasma high-density lipoproteins (HDLs) protect endothelial cells against apoptosis induced by oxidized low-density lipoprotein (oxLDL). The specific component(s) of HDLs implicated in such cytoprotection remain(s) to be identified. Human microvascular endothelial cells (HMEC-1) were incubated with mildly oxLDL in the presence or absence of each of five physicochemically distinct HDL subpopulations fractionated from normolipidemic human plasma (n= 7) by isopycnic density gradient ultracentrifugation. All HDL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 53 publications
8
85
0
2
Order By: Relevance
“…In a more detailed study, HDL subpopulations enriched with apoA-I account for approximately 70 % of the antiapoptotic activity of HDL in a cell culture model with human microvascular endothelial cells that were treated with mildly oxidized LDL. Using rHDL consisting of apoA-I, cholesterol and phospholipids potently inhibited oxLDLinduced apoptosis in these cells (de Souza et al 2010). This suggests that apoA-I plays an important role for the antiapoptotic capacity of HDL in oxLDL-stimulated endothelial cells.…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 79%
See 2 more Smart Citations
“…In a more detailed study, HDL subpopulations enriched with apoA-I account for approximately 70 % of the antiapoptotic activity of HDL in a cell culture model with human microvascular endothelial cells that were treated with mildly oxidized LDL. Using rHDL consisting of apoA-I, cholesterol and phospholipids potently inhibited oxLDLinduced apoptosis in these cells (de Souza et al 2010). This suggests that apoA-I plays an important role for the antiapoptotic capacity of HDL in oxLDL-stimulated endothelial cells.…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 79%
“…In the aorta the capacity of HDL to quench endothelial cell apoptosis may therefore represent an antiatherogenic property of HDL (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000). HDL has been shown to attenuate endothelial cell apoptosis induced by different stimuli such as TNF-α, oxLDL, and growth factor deprivation (de Souza et al 2010;Nofer et al 2001;Suc et al 1997;Sugano et al 2000). It has been suggested that HDL may inhibit both death-receptor and mitochondrial-mediated apoptotic pathways.…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Furthermore, HDL functions as a protective factor for the vascular endothelium by mechanisms that involve interactions with signaling receptors and hence go beyond the regulation of cholesterol homoeostasis or the inhibition of oxidation ( Figure 1). HDL induces endothelium-dependent vascular relaxation via increased endothelial nitric oxide synthase (eNOS) phosphorylation and nitric oxide production, 20 and maintains endothelial barrier stability by promoting endothelial cell survival, 21,22 stimulating endothelial junction closure via HDL-bound sphingosine-1-phosphate (S1P), 23,24 and accelerating endothelial cell migration and re-endothelialization of injured arteries. 25,26 Moreover, antiinflammatory activities of HDL in atherosclerosis have been documented.…”
Section: Hdl and Protection Against Cardiovascular Diseasementioning
confidence: 99%
“…HDL particles feature a high level of structural, compositional and functional heterogeneity, differing in physical (shape, size, density, electrophoretic mobility) and biological properties. Interestingly, small, dense HDL3, which feature distinct structure [16,17] and are enriched in several bioactive lipids and proteins [10,18] display enhanced capacity to efflux cellular cholesterol via the ATP-binding cassette transporter A1 (ABCA1) [19,20], to reduce apoptosis in endothelial cells [21] and to protect low-density lipoprotein (LDL) from oxidative stress [22]. The content of major lipid classes per HDL particle typically diminishes with progressive increase in HDL density, reflecting depletion of total lipid relative to protein components [10].…”
mentioning
confidence: 99%